The Role of School Administration Methods in Enhancing Attitudes Towards Vocational Education Among Basic Stage Students in Public Schools in Ajloun Governorate from The Teachers’ Point of View - Bani Fawaz, Ahmad Jumi' Mohamad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify The role of school administration methods in enhancing attitudes towards vocational education among basic stage students in public schools in Ajloun Governorate from the teachers’ point of view. The researcher used the Descriptive approaches, study Sample consisted from (542) Female and male teachers in the basic stage, chosen randomly, to collect data Questioner used, which consisted (27) paragraph. The result of SPSS analysis shown that the degree of the role of school administration methods in enhancing attitudes towards vocational education among basic stage students in public schools in Ajloun Governorate from the teachers’ point of view was High with average (3.72 out of 5), The finding also showed there is no statistically significant differences at (α≤0.05) refers to principals sex (male and female). In addition, there were statistically significant differences refers to principals years of experience in favor of (Less than 10 years). The study recommended a number of recommendations, the most important of which is holding educational courses for students aimed at raising their awareness of the importance of vocational education.